Architecture Characteristics and Technical Trends of UHF RFID Temperature Sensor Chip - Guofeng Zhang; Dehua Wu; Jingdun Jia; Wanlin Gao; Qiang Cai; Wan’ang Xiao; Lina Yu; Sha Tao; Qi Chu (Active and Passive Electronic Components)
The integration of temperature sensor (TS) and UHF RFID technology has attracted wide attention theoretically and experimentally. The architecture, power consumption, temperature measurement range, accuracy, and communication distance are key indicators of the performance of UHF RFID temperature sensor chip (RID-TSC). This work aims to provide a clearer view of the development of UHF RFID-TSC integration technology. After a systematic analysis of the characteristics of ADC, TDC, and FDC used in an integrated TS, the key low-power technologies under different architectures are summarized. Through the observation of the latest researches and commercial products, the development trend of UHF RFID-TSC technology is obtained, including on-chip and off-chip coordination, multiprotocol and multifrequency support, passive wireless sensor intelligence, miniaturization, and concealment.